Munc18 and Munc13 serve as a functional template to orchestrate neuronal SNARE complex assembly - Wang, Shen; Li, Yun; Gong, Jihong; Ye, Sheng; Yang, Xiaofei; Zhang, Rongguang; Ma, Cong (Nature communications, 2019)
The transition of the Munc18-1/syntaxin-1 complex to the SNARE complex, a key step involved in exocytosis, is regulated by Munc13-1, SNAP-25 and synaptobrevin-2, but the underlying mechanism remains elusive. Here, we identify an interaction between Munc13-1 and the membrane-proximal linker region of synaptobrevin-2, and reveal its essential role in transition and exocytosis. Upon this interaction, Munc13-1 not only recruits synaptobrevin-2-embedded vesicles to the target membrane but also renders the synaptobrevin-2 SNARE motif more accessible to the Munc18-1/syntaxin-1 complex. Afterward, the entry of SNAP-25 leads to a half-zippered SNARE assembly, which eventually dissociates the Munc18-1/syntaxin-1 complex to complete SNARE complex formation. Our data suggest that Munc18-1 and Munc13-1 together serve as a functional template to orchestrate SNARE complex assembly. Synaptic exocytosis depends on formation of the SNARE complex but its assembly mechanism is still under debate. Here, the authors identify an interaction between Munc13-1 and synaptobrevin-2 that is critical for the transition of the Munc18-1/syntaxin-1 complex to the SNARE complex.